Women and Finance-Specific Human Capital: Impact of Gender Role Attitudes - Smith, Brianne; Finke, Michael (Journal of Accounting and Finance, 2023)
The benefits and costs of investing in finance-specific human capital are affected by subjective attitudes about the expected improvement in consumption from higher-quality financial decisions and the expected psychic costs of investing. This study investigates how gender role attitudes of women predict their acquisition of finance-specific human capital. Results indicate that women with the most traditional gender role attitudes are less financially literate than women with non-traditional gender role attitudes and men. Gender role attitudes formed early in life explain differences in financial literacy between men and women observed in prior studies. Multivariate analyses that control for attained human capital suggest that traditional gender role attitudes affect finance-specific human capital investment and investment in formal education. Women with traditional gender role attitudes are the least knowledgeable and have the lowest confidence in applying their financial knowledge.